A new species of Psychodinae (Diptera: Psychodidae) from Argentina - Omad, Guillermo Hugo (2014)
A new species of Desmioza Enderlein, 1937 from Argentina is described: Desmioza biancae n.sp. Adults were collected with Malaise traps in the Nahuel Huapi National Park, in the Argentinean Patagonia. This is the third species of the genus described in the Andean region, Patagonian subregion. A dichotomous key for the identification of all known species of the genus is included.